Research of indicators of activity and participation of disabled people living in inpatient social service institutions and families based on the provisions of the international classification of functioning, disability and health - I. S. Ishutina; M. D. Khodakovskii; S. V. Pavlova; A. V. Sokurov; T. V. Ermolenko (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
The right of every person to free movement, choice of place of stay and residence is guaranteed by the UN Convention on the Rights of Persons with Disabilities [1], the Constitution of the Russian Federation [2] and the Law of the Russian Federation of 25.06.1993 No. 5242-1 "On the right of Citizens of the Russian Federation to freedom of movement, choice of place of stay and residence within the Russian Federation" [3]. The priority direction of the State's social policy is to provide all citizens with equal opportunities for access to social, economic, and cultural values, guaranteeing all members of society respect for the individual and respect for everyone's rights. In order to realize their civil rights and duties, disabled people need the support of society and the state. To integrate disabled people with impaired mental functions into society, the indicators of activity and participation of disabled people living in inpatient social service institutions and families based on the International Classification of Functioning, Disability and Health (ICF) were studied. This study is necessary for further selection of citizens with impaired mental functions for accompanied accommodation and determination of the type of escort.Aim. Research of indicators of activity and participation of disabled people living in inpatient social service institutions and families.Materials and methods. The study of activity and participation indicators was conducted in social service institutions of the population of St. Petersburg. The study involved a multidisciplinary team consisting of employees of the G.A. Albrecht Federal State Budgetary Research Center of the Ministry of Labor of Russia and employees of the CSRIDI (teachers, AFC specialists, psychologists, orderlies). The selection of the Center's clients living in families and graduates of inpatient social service institutions who currently live independently was carried out. The study involved 27 people with impaired mental functions of working age (from 17 to 43 years). Methods and principles of medical and social assessment are used to assess the abilities of persons with mental disorders. Interviewing (interviewing) of the surveyed persons, their relatives and guardians, employees of the PSNI. Documentary data collection (collection of necessary information on the documents of the examined persons). Medical assessment of the condition of the examined persons. Expert assessment of the abilities of persons with impaired mental functions using diagnostic tools by a multidisciplinary team. The data from the clients' documentation was recorded in the developed personal cards. General scientific methods (content analysis, analytical, system-structural, comparative, statistical) and methodological methods of systematization, comparison, generalization, interpretation using the standard Excel-7.0 software package for IBM PC are applied.The object of the study. People with disabilities with impaired mental functions who need accompanied accommodation.The subject of the study. Assisted living services required by disabled persons with impaired mental functions.Results. According to the results obtained, 6 (22.2%) people with impaired mental functions have no restrictions in autonomy, which means they do not need periodic or constant support. It is possible for them to use periodic patronage in order to identify difficult life situations. The rest of the persons with mental disorders have different degrees of difficulties of the person's autonomies and need support of different frequency. Of these, 5 (18.5%) have minor difficulties with facial autonomy, 8 (29.6%) have moderate difficulties, 5 (18.5%) have severe difficulties with facial autonomy, and 3 (11.2%) have significant limitations of facial autonomy and need constant care. It is worth noting that three disabled people with impaired mental functions, two of whom, according to the results of the study, were in the group of persons with severe difficulties of facial autonomy, and one with moderate difficulties of facial autonomy have significantly pronounced disorders of neuromuscular, skeletal and movement–related functions, which is why they constantly need help when moving. At the same time, they have mastered secondary general education, can read, count, performs written and oral commands, is able to maintain a conversation, is able to build interpersonal interactions. To clarify the degree of violation of the person's autonomy and the need for support in the presence of restrictions on independent movement, the b760 domain "Control of voluntary motor functions" and the domains of the "Mobility" section were calculated separately.Discussion. The development and implementation of an assessment system for disabled people based on the study of indicators of functioning, activity and participation of citizens with impaired mental function with an assessment of medical and social factors affecting their livelihoods and an assessment of the degree of autonomy of persons living in inpatient social service institutions and families will solve questions about the form of life of citizens suffering from mental disorders, and organize work on their employment.Conclusions. Depending on the indicators of activity and participation of disabled people living in inpatient social service institutions and families, based on the provisions of the international classification of functioning, disability and health, it allows you to determine the degree of expression of a person's autonomy, the volume and duration of support services.